Influencing factors of the future utilisation of construction robots for buildings: A Hong Kong perspective. (July 2020) - Pan, Mi; Linner, Thomas; Pan, Wei; Cheng, Hui-min; Bock, Thomas
Abstract : Construction robots are expected to have disruptive impacts on the building industry, but there is still a lack of utilisation. While significant attention has been paid to technical advancement, little has been done to comprehensively understand the broader societal issues associated with the use of this technology. This paper aims to provide a holistic exploration of the influencing factors of the future utilisation of construction robots in a systems manner, analyse the interactions among these factors and identify the key ones that are most influential in shaping the technological transformation. A modified fuzzy decision-making trial and evaluation laboratory (DEMATEL) method is developed and applied. Hong Kong was selected as the desirable case for the study due to its vibrant yet challenging built environments. Factors were first systematically identified and synthesised before being empirically verified, evaluated and analysed through the modified fuzzy DEMATEL. The results demonstrate the multi-faceted and complexly interrelated factors influencing the utilisation of construction robots. Eleven influencing factors were determined as critical for shaping the future trajectory of robotic applications, among which "construction cost", "governmental support" and "the scale of prefabrication" are the most influential ones. The findings indicate that more interdisciplinary efforts and broader non-technical discussions are needed to achieve the successful transition of the industry towards robotic construction. The findings further reveal the driving forces of environmental pressures behind the future utilisation of construction robots. Detailed utilisation scenarios which fit to the evolution of the whole society are recommended for future research. Highlights: A systems perspective is applied on the future utilisation of construction robots. A modified fuzzy DEMATEL method is proposed for influencing factor analysis. Eleven key influencing factors are identified to shape the trajectory of construction robots' utilisation. Environmental pressures were found to actively drive the utilisation of construction robots. Broader, non-technical factors are critical to the future utilisation of construction robots.